Deciphering the physicochemical and microscopical changes in Ganoderma boninense-infected oil palm woodblocks under the influence of phenolic compounds - Surendran, Arthy; Siddiqui, Yasmeen; Ahmad, Khairulmazmi; Fernanda, Rozi (Multidisciplinary Digital Publishing Institute, 2021)
The threat of Ganoderma boninense, the causal agent of basal stem rot disease, in the oil palm industry warrants finding an effective control for it. The weakest link in the disease management strategy is the unattended stumps/debris in the plantations. Hence, this study aimed to determine whether the selected phenolic compounds could control G. boninense in inoculated oil palm woodblocks and restrict wood biodegradation. Results indicated a significant reduction in the wood mass loss when treated with all the phenolic compounds. Surprisingly, syringic and vanillic acids behaved ambivalently; at a lower concentration, the wood mass loss was increased, but it decreased as the concentrations were increased. In all four phenolic compounds, the inhibition of mass loss was dependent on the concentration of the compounds. After 120 days, the mass loss was only 31%, with 63% relative degradation of lignin and cellulose, and 74% of hemicellulose and wood anatomy, including silica bodies, were intact in those woodblocks treated with 1 mM benzoic acid. This study emphasizes the physicochemical and anatomical changes occurring in the oil palm wood during G. boninense colonization, and suggests that treating oil palm stumps with benzoic acid could be a solution to reducing the G. boninense inoculum pressure during replantation in a sustainable manner.